Pengaruh Income Smoothing terhadap Agresivitas Pajak dengan Corporate Governance sebagai Variabel Moderasi - Servina Nadya Serli; Siti Isnaniati; Rike Selvia Sari (Jurnal Proaksi, 2025)
Main Purpose -  The objective of this study is to analyze the effect of Income Smoothing on Tax Aggressiveness with Corporate Governance as a moderating variable.Method -  This study uses a quantitative approach. It uses secondary data in the form of annual reports of manufacturing companies listed on the Indonesia Stock Exchange from 2022 to 2024. The research sample was selected using purposive sampling, resulting in 58 companies with a total of 174 data points. The data was analyzed using IBM SPSS 25 software. Main Findings -  The results of this study indicate that corporate governance moderates the effect of income smoothing on tax aggressiveness—where income smoothing lowers the ETR, while more effective governance weakens this effect.Theory and Practical Implications -  These findings reinforce the agency framework, whereby strong governance limits managerial opportunism in profit management and tax strategies. From a policy perspective, regulators and issuers need to strengthen the independence of commissioners and increase the transparency of tax policies to reduce tax aggressiveness.Novelty -  This study raises the variable of Corporate Governance as a moderating variable in the influence of Income Smoothing on Tax Aggressiveness, which is new and has not been studied before.